Primerjava dveh teoretičnih modelov in teorije zdravstvene nege preko konceptov metaparadigme - Babuder, Dragan (Obzornik zdravstvene nege, 2015)
Introduction: Selection of a suitable theoretical model or theory of nursing is the basis for good practice. In Slovenia, Virginia Henderson's nursing model has been adopted as a base for professional nursing practice. The aim of this article is to present an organised and practical overview of the strengths and weaknesses of Henderson's nursing need theory in comparison to Hildegard E. Peplau's theory of interpersonal relations and Imogene M. King's goal attainment theory, as well as their implications for practice. Methods: The descriptive method was used with a literature review of domestic and foreign professional and scientific literature. The technique of critical reading was employed to study all the relevant accessible published sources. Web searching was conducted through COBIB.SI data base and data bases such as Jupsline, Medline and CINAHL. The results are compared in terms of the theories' utilization and application following Jacqueline Fawcett's framework for evaluation. Results: All three nursing theories presented are applicable at all levels of nursing practice. Nursing is a major concept in all three theories and health is the goal for all three theorists. The concept of environment is poorly described. Discussion and conclusion: The research into the application of nursing models and theories in recent years is scarce. Nurses should commit to further research and development of nursing theories to generate and test the theories and their practical application.
Keywords: evaluation; Hildegard E. Peplau; Imogene M. King; medicinske sestre; nurses; nursing; teorije; theories; uporabnost; usefulness; Virginia Henderson; vrednotenje; zdravstvena nega